The association between Metabolic Score for Visceral Fat and depression in overweight or obese individuals: evidence from NHANES - Liu, Heng; Dong, Huqiang; Zhou, Yu; Jin, Mingchu; Hao, Haidong; Yuan, Yutang; Jia, Hongtao (Frontiers in Endocrinology, 2024)
Background: Depression is a common mental illness with a high prevalence in overweight or obese individuals. Recent studies suggest that the Metabolic Score for Visceral Fat (METS-VF) is a novel metric for assessing visceral fat levels, potentially linking metabolic disturbances to depression. This study explores the association between METS-VF and depression severity in overweight or obese U.S. adults.: Data were obtained from the National Health and Nutrition Examination Survey (NHANES) 2007-2018 dataset, including 9,415 overweight or obese participants. Depression severity was measured using the Patient Health Questionnaire-9 (PHQ-9). To assess the association between METS-VF and depression, the study methodology included multivariate logistic regression, subgroup analyses, generalized additive model (GAM), and smoothed curve fitting. This study also calculated BMI for the Non-Hispanic Asian population from 2011-2018 and incorporated this data as part of a sensitivity analysis. Results: Elevated levels of METS-VF in overweight or obese participants were significantly associated with increased PHQ-9 scores and an increased likelihood of 2 / 20 depression. Notably, this association remained significant after adjustment for multiple covariates. Smoothed curve-fitting plots showed no nonlinear association between METS-VF and PHQ-9 scores. Subgroup analyses confirmed the robustness of these results across populations, particularly among people under the age of fifty. The sensitivity analyses confirmed the robustness of the results in this study. Conclusion: METS-VF levels were positively associated with depression severity and the likelihood of depression in overweight or obese individuals, with the association being particularly pronounced in people under 50 years of age.